Mahar dalam Islam: Hukum, Tuntutan, dan Realitas Sosial - Khairuddin, Khairuddin (Islamic Family Law Department, Sharia Faculty, Stai Syekh Abdur Rauf, Aceh Singkil, 2024)
This study aims to analyze the position of dowry in Islamic law, the demands of sharia regarding the ideal dowry, and its relevance to the social reality of contemporary Muslim society. Dowry is seen as a symbol of appreciation for the wife and a sign of seriousness in marriage, as well as a wife's right that must be fulfilled by the husband. Islamic sharia emphasizes that the amount of dowry should be adjusted to the husband's ability without burdening him, prioritizing the principles of simplicity and balance that are relevant to social and economic conditions. The research used is a qualitative approach with library research. The findings of this study show that the value and form of dowry in contemporary Muslim society vary due to the influence of local culture, economic conditions, and community expectations. Sometimes, the high demand for dowry is a barrier for couples who want to get married. Therefore, a deeper understanding of the essence of dowry is needed, in order to be in accordance with the demands of sharia while at the same time being able to adjust to the social reality that is developing today. [Penelitian ini bertujuan untuk menganalisis kedudukan mahar dalam hukum Islam, tuntutan syariat tentang pemberian mahar yang ideal, serta relevansinya dengan realitas sosial masyarakat Muslim kontemporer. Mahar dipandang sebagai simbol penghargaan kepada istri dan tanda keseriusan dalam pernikahan, serta merupakan hak istri yang harus dipenuhi oleh suami. Syariat Islam menekankan agar besaran mahar disesuaikan dengan kemampuan suami tanpa membebani, mengedepankan prinsip kesederhanaan dan keseimbangan yang relevan dengan kondisi sosial dan ekonomi. Penelitian yang digunakan adalah pendekatan kualitatif dengan metode library research. Temuan penelitian ini menunjukkan bahwa nilai dan bentuk mahar dalam masyarakat Muslim kontemporer mengalami variasi akibat pengaruh budaya lokal, kondisi ekonomi, serta ekspektasi masyarakat. Kadangkala, tingginya tuntutan mahar menjadi penghalang bagi pasangan yang ingin menikah. Oleh karena itu, diperlukan pemahaman yang lebih mendalam tentang esensi mahar, agar sesuai dengan tuntutan syariat sekaligus mampu menyesuaikan dengan realitas sosial yang berkembang saat ini].